Preference reversal in intertemporal decision making - Zhou, Yan-Bang; Zhang, Kun; Zhai, Hong-Kun; Bao, Qing; Xiao, Shanshan; Dang, Junhua (Frontiers in Psychology, 2024)
This study examines asymmetric preference reversals in intertemporal decision-making by comparing gain and loss contexts across choice and bidding tasks. In the gain context, participants preferred smaller, sooner (SS) rewards in choice tasks but assigned higher valuations to larger, later (LL) rewards in bidding tasks. Conversely, in the loss context, they showed a preference for LL options in choice tasks but provided lower bids for SS options. Bidding tasks consistently required longer decision times than choice tasks, indicating greater cognitive demands during valuation processes. A real-world questionnaire involving 370 participants validated these findings across economic and health-related scenarios. These results underscore the role of task formats in shaping preferences, offering practical insights for refining strategies in behavioral decision-making and applied contexts.